Ordre social, ordre spatial : territorialisation des politiques de sécurité publique à Rio de Janeiro - Justine Ninnin (EchoGéo, 2014)
Public security is a challenge in Brazil, especially in Rio de Janeiro. The city, which seeks to be a central player on the international scene has redefined its security strategy by reaffirming the public authorities power in the favelas through “militarization” and territorialised policy. The favelas which have been stigmatized and abandoned by the government, have drifted under the control of armed criminal groups. Through the establishment of a community policing for 2008, the pacification of the favelas began to rebuild a more competent, more transparent and less repressive police.